MULTITERRITORIALIDADES NA GESTÃO DA PROTEÇÃO SOCIAL NO ESTADO DA PARAÍBA, BRASIL - Marinalva Conserva (Universidade Federal do Maranhão, 2018)
The proposed debate on the management of social protection policies in Brazil is based on the assumption: to multiterritorialities, they make cleavage withthe demands for protection linked to the housing territory of families that use public policies, especially the beneficiaries of Income Transfer In the state of Paraíba. This sample-based study, with the beneficiary families, in rural and urban areas, allows us to elucidate in terms of findings: territorial singularities and conditions produce (re)significations in relation to the materiality of social protection, object of the Public Assistance Policy Social Security and Income Transfer Programs. And, in turn, it produces demands and challenges in the contribution of strategies and tools of the territorialized management of social protection in the perspective of the affirmation of social equity as a right.